Mute swans - Pfeffer, Wendy, 1929- (Parsippany, NJ : Silver Press, 1997)
Discuses the characteristics and life cycle of the Mute Swan.
School Library Journal
Appraisal-Science Books for Young People
The Science Teacher (N.S.T.A.)
2.8
K-3
Keywords: Mute swan -- Juvenile literature; Mute swan; Swans; Mute swan; Swans